DEVELOPMENT OF DIGITAL MARKETING IN E-COMMERCE (International journal of artificial intelligence, 2025)
This article examines the trends and developments in digital marketing in the e-commerce sector . It emphasizes the role of digital technologies and promotion tools in improving the efficiency of online sales and developing competitive advantages for companies. Particular attention is paid to areas such as the use of Big Data , artificial intelligence (AI), content personalization, and marketing process automation are explored. The prospects for digital marketing development in the context of increasing digitalization and changing consumer behavior are also analyzed.